The 2019 annual meeting of the European Academy of Facial Plastic Surgery: an otolaryngology resident perspective as a first-time attendee and the importance of in person attending of such meetings - Saadoun, Rakan; Risse, Eva-Maria (Facial plastic surgery, 2021)
Thieme E-Books & E-Journals
Gesehen am 12.01.2022
Letter to the editor